Determinant of zinc deficiency in orthopaedic inpatients - Daisuke Iida; Tomonori Shigemura; Yohei Yamamoto; Miki Morimoto; Yasuaki Murata (PLoS ONE, 2025)
Zinc is vital for over 300 enzymes in major metabolic pathways, and deficiency can lead to serious conditions, especially post-surgery. This study aimed to investigate predictive factors of zinc deficiency in orthopaedic inpatients. A retrospective case-control study was conducted on patients admitted to Teikyo University Chiba Medical Center from 15 February to 31 August 2022. Patients were divided into zinc deficiency (< 60 µg/dL) and non-deficiency groups. Data included demographics, comorbidities, hospitalisation reasons, fracture details, medication use, and laboratory values. Fisher’s exact test and two-sample t-tests were used for analysis. Of 156 patients, 47 (30.1%) had zinc deficiency. The case group had higher fracture rates (68.1% vs. 33.9%; p < 0.001), and lower rates of spinal disease (2.1% vs. 31.2%; p < 0.001) and osteoarthritis (8.5% vs. 22.9%; p = 0.04). Fragility and hip fractures were more common in the case group. Anaemia, hip fracture, and hypoalbuminaemia were independent predictive factors of zinc deficiency.